2016
DOI: 10.1039/c6ra14008d
|View full text |Cite
|
Sign up to set email alerts
|

Black phosphorus crystal as a saturable absorber for both a Q-switched and mode-locked erbium-doped fiber laser

Abstract: We report a simple way to generate Q-switched and mode-locked pulses by incorporating black phosphorus (BP) as a saturable absorber (SA) in an erbium-doped fiber laser (EDFL) cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…[16][17][18][19][20][21] BP-SA can be manufactured via liquid phase exfoliation technology 14 or the mechanical exfoliation method. 22 Zhang et al reported few-layer selenium-doped black phosphorus with high quality and low cost in 2017. 23 However, avoiding oxidation and preventing optical damage to the BP-SA still limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21] BP-SA can be manufactured via liquid phase exfoliation technology 14 or the mechanical exfoliation method. 22 Zhang et al reported few-layer selenium-doped black phosphorus with high quality and low cost in 2017. 23 However, avoiding oxidation and preventing optical damage to the BP-SA still limit its application.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of saturable absorbers based on Cr 2+ -doped crystals are high ground-state absorption cross-sections (~10 −19 cm 2 ) and negligible excited-state absorption losses [12]. Recently, 1.5-1.6 μm passively Q-switched operation has been demonstrated using a number of different novel 2-D materials like singlewalled carbon nanotubes, graphene, topological insulators, transition-metal di-chalcogenides and black phosphorus [13][14][15][16][17][18][19][20]. However, these experiments resulted in rather low laser pulse energies typically not exceeding ~1 µJ.…”
Section: Introductionmentioning
confidence: 99%
“…According to the compactness, simplicity and flexibility design, passive technique of acquiring Qswitched pulses have more attention compared to active technique. Pulses can be found using various kinds of saturable absorbers including graphene oxide, Transition metal dichalcogenides (TMDs) such as molybdenum disulfide (MoS2), Semiconductor Saturable Absorption mirrors (SESAMs), and Carbon Nano-Tube (CNT) [1][2][3]. However, these saturable absorbers have a number of drawbacks in terms of their fabrications and compatibility with some optical fiber applications, it also suffers low pulse energy with a wide band gap between layers.…”
Section: Introductionmentioning
confidence: 99%
“…As the result of graphene limitations, transition-metal dichalcogenides have been studied due to their result of special absorbing and relying on bandgap thickness. BP saturable absorber has joined the family of 2D material with more efficient than the above-mentioned SA in terms of band gap filling [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%